THE IMPORTANCE OF SKILLS IN CAREER DEVELOPMENT - TODERICIU Ramona; GRAMA Blanca (Management of Sustainable Development)
The purpose of this paper is to investigate how individual career management is related to career sustainability, analyzing the role of skills in career development. The study surveyed 120 employees, collecting data through a structured questionnaire. The findings highlight the essential role of skills in creating and maintaining a competitive advantage in the labor market. This research adds to the growing body of literature by empirically validating the importance of skills in competitive strategy and provides practical implications for managers seeking to leverage these resources for sustained competitive success.